Characterization of hydrocarbon utilizing bacteria in waste engine oil-impacted sites - Iniobong Ime James; Mayen Godwin Ben; Agnes Monday Jones; Patience Saturday Akpan; Idorenyin Idorenyin Eka; Albert Ema Oruk; Aniefon Alphonsus Ibuot (Highlights in BioScience, 2020)
Changes in soil physicochemical properties and bacterial species present in soil contaminated with waste engine oil were evaluated at three auto-mechanical workshops in Uyo, Nigeria. This work was aimed at isolating and identifying hydrocarbon degrading bacteria from waste engine oil polluted soil, and assessing their hydrocarbon-utilizing ability. Waste engine oil pollution affected soils significantly with increases in soil physicochemical properties, and heterotrophic bacterial population counts. Eight bacterial speciesCorynebacterium kutscheri, Pseudomonas aeruginosa, Flavobacterium aquatile, Serratia odorifera, Micrococcus agilis, Staphylococcus aureus,Micrococcus luteus and Bacillus substilis were isolated by the selective enrichment technique and screened for hydrocarbon utilization capability in mineral salt media with 1% (v/v) waste engine oil as a sole carbon and energy source. The extent of bacterial growth observed was related to the ability of organisms to biodegrade hydrocarbons present in the medium bacterium species, which showed varying hydrocarbon utilization during the 15 days of incubation. Growth in hydrocarbon medium was the most efficient in cultures of Corynebacterium kutscheri. All isolates also showed variable emulsification ability, with Corynebacterium kutscheri, showing the highest ability. These results demonstrate the presence of indigenous bacteria in hydrocarbon-polluted soils and the potential toward the remediation of hydrocarbons.